Pycnogonids (Arthropoda: Pycnogonida: Pantopoda) from the Banderas Bay, Mexican Pacific Coast - Villatoro-Ortiz, Alejandrina (2022)
This study reports the composition of pycnogonid species associated with the fouling fauna on the docks of a tourist marina collected in September and October 2011 and Abril and June 2012, as well as the samples of algae, dead coral, and chaetopterid tubes collected by free diving at beach sites from February to April 2018. The sites studied, La Cruz de Huanacaxtle marina and surrounding beaches, are located along the Mexican Pacific, on the north coast of the Banderas Bay in the State of Nayarit. A total of 78 specimens were examined belonging to five families, six genera, and nine species. A systematic list is presented, and each species includes a brief description, information on its distribution and abundance in the studied sites. In the Cruz de Huanacaxtle marina docks, 56 organisms were recorded corresponding to three species. Eight species were found on the La Manzanilla, Burros, La Lancha and Isla María Cleofás beaches, six of which were not present on the docks. The most abundant species were Anoplodactylus sp. with 32 organisms (41%) and Nymphon lituus with 24 (31%), the latter dominant in the docks of the marina. This study constitutes the first record of pycnogonids for the north coast of the Banderas Bay, Mexico. It contributes to the knowledge of the biodiversity of the central Mexican Pacific coast and documents the pycnofauna associated with biofouling communities of a nautical marina.